Granulomatosis with polyangiitis: Rapidly progressive necrotizing glomerulonephritis in a pediatric patient - Luna, Maria (2014)
Granulomatosis with polyangitis (GPA) is associated with a broad range of clinical manifestations including renal disease. It is a systemic vasculitis that is rarely encountered in children. We present a 14-year-old girl who suffer for pharyngitis one week before. She was admitted for macroscopic hematuria and oliguria, under the possibility of nephritic syndrome.Renal failure with rapidly progressive glomerulonephritis ocurred within 24hour. Immunologic tests showed the presence of type-C anti-neutrophil cytoplasmic antibodies(c-ANCA with antiproteinase 3 specificity) and renal biopsy revealed pauci immune crescentic focal necrotizing glomerulonephritis. Treatment including methylprednisolone and cyclophosphamide intravenous pulses allowed renal recovery after 3 weeks. The clinical, haematological and biochemical parameters improved substantially acheiving remission. Granulomatosis with poliangeitis, although rare in children, should be considered in the above clinical scenario. This case underlines that knowledge of renal histology diagnosis and an early aggressive immunosuppressive therapy are essential for the management of these patients.